Introduction: Dante as Mediator and Dante's Mediators. (3rd April 2022) - Bowe, David; Coluzzi, Federica
ABSTRACT: This issue explores what it means to mediate a cultural artefact across forms, times, and disciplines. Using the works of Dante as a shared case study, the articles analyse different modes of mediation – rewriting, adaptation, illustration, translation, and modes of authorial mediation – as evident in the seven centuries of critical, creative, and readerly response to Dante's works, especially, but not exclusively, his Commedia . This introduction indicates sources and implications for 'mediation' as it is articulated across the issue: from Roland Barthes, Gabriele D'Annunzio and contemporary videogames to medieval and modern illuminated manuscripts and illustrations. We draw out the underlying connections between Dante's own role as mediator and expectations for mediation of his works, as in his self-commentary, his frequent addresses to readers (contemporary and future) and the multiple media invoked in his writings and the ways in which subsequent mediators of Dante have responded to these calls.